AMPLIFICATION OF ISLAMIC DOCTRINES IN HADITH MEMES PROHIBITION OF WOMEN TRAVELS WITHOUT A MAHRAM ON INDONESIAN SOCIAL MEDIA - Miski Miski (UIN Sunan Kalijaga Yogyakarta, 2021)
This paper is a netnographic study of hadith memes prohibition women from traveling without mahram on Indonesian social media. there are three main questions that are in focus: 1) how does classical literature record hadiths related to this theme? 2) how does this hadith exist in memes on Indonesian social media? 3) how did this phenomenon give birth to the amplification of Islamic doctrine? By using content analysis, this study shows: 1) the hadith in this theme is a hadith that is widely known among the Companions of the Prophet and the gatherers of the hadith, and is considered mutually reinforcing, 2) on social media, the hadith exists in various memes; besides the media factor, also the factors of its users which still carry theological aspects, 3) the massive spread of memes in this theme triggers the creation of the Islamic doctrine, and has an effect on the neglect of other more essential aspects of Islamic doctrine. This study also found that the existence of the meme hadith is a re-actualization of classical discourse that is intended as resistance to a variety of religious social phenomena that are deemed deviant, especially in relation to women's freedom in the public sphere. To this point, it must be acknowledged that the memes that are spread are methodologically problematic or irrelevant in a contemporary context. Beyond these findings, the existence of memes with different interpretations but in limited quantities and intended as a counter to memes that have been widespread will further enrich the discourse of hadith studies. Keywords: hadith, memes, netnographic study, mahram